2005
DOI: 10.1021/ja052477m
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ion Responsive DNA Binding in a Zinc Finger Fusion Protein

Abstract: Zinc finger fusion proteins, having a Ca-binding site from troponin C, were created to develop Ca-responsive regulation of DNA binding. The typical zinc finger folding of a novel fusion protein with a single finger, F2-Tn, was investigated using UV-vis spectroscopy of the Co-substituted form and CD experiments. Detailed structural analyses of F2-Tn/Zn2+ using NMR experiments and structural calculations clarify that our fusion protein gives a native zinc finger folding with the artificial Ca-binding domain inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…To further investigate the regulation of OmpA by SmpB, we monitored the fluorescence activities of the P ompA and EGFP translational fusion in the presence or absence of SmpB expression. It has been reported that divalent metal ion Mg 2+ or Ca 2+ stabilized the molecule conformation and affected interactions through neutralizing the negative charges ( Lusetti et al, 2003 ; Onoda et al, 2005 ; Ralec et al, 2017 ; Kim et al, 2018 ). Hence, divalent metal ion Mg 2+ or Ca 2+ was added and the results demonstrated all the cells maintained constant growth ( Figure 2A ), while the cells expressing SmpB showed the significant fluorescent enhancement when supplemented with 5 mM Mg 2+ compared with the controls ( Figure 2B ), signifying Mg 2+ may help to stabilize the binding of protein and DNA structure.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the regulation of OmpA by SmpB, we monitored the fluorescence activities of the P ompA and EGFP translational fusion in the presence or absence of SmpB expression. It has been reported that divalent metal ion Mg 2+ or Ca 2+ stabilized the molecule conformation and affected interactions through neutralizing the negative charges ( Lusetti et al, 2003 ; Onoda et al, 2005 ; Ralec et al, 2017 ; Kim et al, 2018 ). Hence, divalent metal ion Mg 2+ or Ca 2+ was added and the results demonstrated all the cells maintained constant growth ( Figure 2A ), while the cells expressing SmpB showed the significant fluorescent enhancement when supplemented with 5 mM Mg 2+ compared with the controls ( Figure 2B ), signifying Mg 2+ may help to stabilize the binding of protein and DNA structure.…”
Section: Resultsmentioning
confidence: 99%
“…The bands were quantified with FUJI FILM Science Lab 2001 Image Gauge software. The binding ratio of FLAG-p53 to target DNA was calculated using equation R = I b /( I b + I f ), where I b and I f are the intensities of FLAG-p53-bound and free DNA bands, respectively [50, 51]. …”
Section: Methodsmentioning
confidence: 99%
“…The three‐dimensional structure of the peptide was calculated from the experimental constraints using the simulated annealing method with XPLOR (version 3.851)32. The calculation was performed according to a similar procedure described previously 33, 34. The structures and structural parameters were analyzed using PROCHECK‐NMR (Table 2)35.…”
Section: Methodsmentioning
confidence: 99%